Determinants of pika population density vs. occupancy in the Southern Rocky Mountains. Issue 3 (1st April 2014) - Erb, Liesl P.; Ray, Chris; Guralnick, Robert
Abstract : Species distributions are responding rapidly to global change. While correlative studies of local extinction have been vital to understanding the ecological impacts of global change, more mechanistic lines of inquiry are needed for enhanced forecasting. The current study assesses whether the predictors of local extinction also explain population density for a species apparently impacted by climate change. We tested a suite of climatic and habitat metrics as predictors of American pika ( Ochotona princeps ) relative population density in the Southern Rocky Mountains, USA. Population density was indexed as the density of pika latrine sites. Negative binomial regression and AICc showed that the best predictors of pika latrine density were patch area followed by two measures of vegetation quality: the diversity and relative cover of forbs. In contrast with previous studies of habitat occupancy in the Southern Rockies, climatic factors were not among the top predictors of latrine density. Populations may be buffered from decline and ultimately from extirpation at sites with high‐quality vegetation. Conversely, populations at highest risk for declining density and extirpation are likely to be those in sites with poor‐quality vegetation.